STUDY ON FORMULATION OF POLYURETHANE/CLAY NANOCOMPOSITES BASED ON PALM OIL POLYOL - Rihayat, Teuku; Mustapha, Saari B.; Mahmood, Mohd Hilmi B; Wan Yunus, Wan MD Zin; Rashid, Suraya Abdul; Zaman B, Khairul; Hj. Mohd. Dahlan, Hj. Mohd. Dahlan (Jurnal Sains dan Teknologi Reaksi, 2005)
A novel segmented polyurethane/clay nanocomposites has been synthesized by polyurethane based on palm oil and Kunipia-F as organoclay with an ammonium salt of cetyltrimetyl ammonium bromide (CTAB). In this investigation, we give much interest to synthesis of polyurethane/clay based on palm oil as raw materials for polyols to open new era for partial replacement of petrochemical based polyol with palm oil based polyols. Surprising, we got the polyurethane elastomer after along time polyurethane based on palm oil only using in coating applications. However, it is the first report in investigation about polyurethane/clay nanocomposites based on palm oil. Polyurethane/clay nanocomposites were prepared by a pre-polymer method and evaluated by fourier transform infrared spectra (FTIR) and X-ray diffraction measurements (X-RD) respectively.Keywords : Nanocomposite, polyurethane, synthesis, palm oil